Energy innovation market: analysis of trends and functioning issues - Pimonenko, Tetyana; Lyulyov, Oleksii; Ziabina, Yevheniia; Vasylyna, Tetiana (Herald of Economics, 2022)
Introduction. The accepted Green Deal Policy led to the rapid development of energy innovations that reduce greenhouse gas emissions and increase the countrys energy efficiency and energy security.The paper aims to analyze the trends, bottlenecks and problems of the energy innovation market in Ukraine and EU to determine the likelihood of achieving target indicators such as the Green Deal Policy and the Energy Strategy of Ukraine until 2035.Research methods. The study applied bibliometric analysis to systematize the theoretical framework in the analysis of the energy innovations. Besides, the authors applied the following methods: logical generalization, scientific abstraction, system- structural analysis.Results. In 2021, Mission Innovation member countries have invested more than 27 billion in clean energy research and development. The United States had the largest increasing in funding for research and development in energy innovation. In second place the People’s Republic of China. The findings showed that the energy innovations market in both the EU and Ukraine is not going according to the declared goals. First of all, experts attribute these gaps (the difference between current and planned targets) to the COVID-19 pandemic. The ability to bring new technologies to market will be weakened as a result of pandemic failures. In addition, market and political uncertainty threatens to reduce the resources available to entrepreneurs to study energy innovation. Perspectives. It is established that the policy of energy innovation development should be developed taking into account the possible explicit / latent and positive / negative transmission effects in the chain “business-government-society”. In addition, this policy should be consistent with the goals of the energy transition, ensure the competitiveness and technological security of the countries. The results showed that further research requires tools to stimulate the development of energy innovation in Ukraine based on the generalization of best practices of leading countries in the implementation of energy innovation.